Proceedings Of The Seventy-Sixth Regular Meeting Of The Rocky Mountain Coal Mining Institute Lionshead Village, Vail, Colorado June 29-July 2, 1980 - Morning Session Monday, June 30, 1980 (Rocky Mountain Coal Mining Institute, 1980)
The 76th Regular Meeting of The Rocky Mountain Coal Mining Institute convened at The Mark Conference Center, Lionshead Village, Vail, Colorado, and was in session at 9:30 a.m. A film-"Once Upon a Time" showing the stifling effect of unnecessary government regulations and the importance of protecting economic political freedoms was shown. Past President, Robert E. Murray, President, Western Division and Subsidiary Companies, The North American Coal Corporation, called the meeting to order. He introduced President Loren V. Linville, District Sales Manager, Industrial Products Division, Uniroyal, Inc. A biographical sketch follows: Loren V. Linville was born on December 29, 1925 on the family farm near Wiley, Colorado to Scott W. and Hazel Linville. He has one sister, a teacher in the public schools and a brother who is an optometrist in Gustine, California. Loren grew up in Lamar, Colo. graduating from Lamar High School in 1944 and spent the folllowing 2 years as a radioman in the US Navy. He graduated from Denver University in 1950 with a BS in Mechanical Engineering. On September 12, 1948 he married Norma. They have 3 children, Linelle, a teacher in New Mexico, Bruce an electronic technician in Colorado Springs and Kevin at home.